Investigating the influence of brand effect and personality traits towards purchase intention of limited edition of luxury brands - Sutrisna, Elaine (2015)
This paper aims to examine the effect of attitude, subjective norm and perceived behavioural control towards purchase intention of limited edition of luxury brands as supported by the Theory of Planned Behaviour. Two studies were conducted to measure the influence of brand effect on purchase intention by comparing non-fictitious brands (Louis Vuitton) and fictitious brands (Touché). Supported by Social Cognitive Theory, the influence of the personality factors and subjective norm on attitude was also investigated. Theoretically, this study closed inherent gaps as identified by the literature. Managerially, this study contributed in profiling limited edition of luxury brands consumers and identifying strategies to attract consumers in purchasing limited edition products